The Impact of The Use of Accounting Information and Environmental Uncertainty on The Success of Small and Medium Enterprises (SMEs) - Karina Silaen; Arisman Parhusip; Montaris Silaen (CV. ADMITECH SOLUTIONS, 2025)
This study aims to analyze the influence of accounting information usage and environmental uncertainty on the business success of SMEs in Medan City. The research employs a quantitative method with a t-test approach to test the hypotheses. The results indicate that accounting information usage does not have a significant impact on business success, as evidenced by a significance value of 0.805 (>0.05), leading to the rejection of the first hypothesis (H1). Conversely, environmental uncertainty has a positive and significant effect on SME business success, with a significance value of 0.001 (<0.05), confirming the acceptance of the second hypothesis (H1). These findings suggest that in uncertain environments, SMEs in Medan City need more flexible adaptation strategies to sustain and enhance their business success. Additionally, although accounting information is an essential factor in business management, this study's results indicate that its usage does not directly impact SME success in Medan City. Therefore, a more comprehensive approach to implementing accounting information is needed to provide more tangible benefits for small and medium-sized enterprises.